Operationalizing Experience: Donor Approaches to Service Delivery in Fragile States - Alisa DiCaprio (Asian Development Bank (ADB), 2013)
This study explores the different approaches to service delivery in fragile states by surveying donors' own evaluations of their existing fragile states policies. Because there is limited understanding of what works in risky environments, monitoring and evaluation are critical components of effective assistance. By highlighting trends in the strategies that donors have developed to implement acknowledged good practices, we can better understand how these experiences might contribute to future project and evaluation design.
hdl:11540/2091
Keywords: H41; H84; I38; O19; O22; 330; fragile states; donor policy; foreign aid; healthcare; water and sanitation; security and justice; education; Gesundheitsversorgung; Wasserversorgung; Kanalisation; Soziale Sicherheit; Bildungswesen; Staatskrise; Politische Instabilität; Institutionelle Infrastruktur; Entwicklungsländer; Welt